C-REACTIVE (CRP) PROTEIN IN TRANSFUSION DEPENDENT THALASSAEMIC PATIENTS - Jokhio, Rukhsana; Khan, Yaqoub; Chughtai, Latafat Ali; Mughal, Zaib un-Nisa (Pakistan Journal of Physiology, 2009)
Background: In thalassaemic patients iron overload, secondary to blood transfusion, results toxic effects by producing reactive radicals. Iron overload can be studied using serum ferritin level which has a direct correlation with the body’s iron status. While oxidative damage can be studied using biomarker of inflammation like hsC-reactive proteins. Methods: Blood samples of 55 thalassaemic patients (39 males, 16 females) were collected from Fatmid Foundation (Hyderabad). The samples were analysed for CBC, serum ferritin level and hsC-reactive proteins. Results: High mean serum ferritin levels was found in all the patients regardless of the frequency of blood transfusion (4774.2135±3143.3040 µg/L), indicating the iron overload. High mean hsC-reactive protein was found (2.5151±1.3712) with a positive correlation with ferritin (r= 0.8371198, p= 0.0000) and platelets (r= 0.43293443, p= 0.000962175). Conclusion: C-reactive proteins serve as biomarker of various inflammatory conditions, progression of cardiovascular diseases and as indicator of morbidity and mortality. High C-reactive proteins in these patients indicate ongoing iron overload toxicity related damage in these patients. The estimation of hsC-reactive proteins and other biomarkers of inflammation and oxidation may help in better management of these patients.